PENERAPAN MODEL ROTATING TRIO EXCHANGE DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP SISWA DI SMA MUHAMMADIYAH 1 PALEMBANG - Habibur Rachman; Fajri Ismail; Muhammad Win Afgani (ADIBA : JOURNAL OF EDUCATION, 2023)
Researchers in this thesis are motivated by the low learning outcomes of Islamic Religious Education by students because students are less motivated to learn Islamic Religious Education and because the learning model used by teachers has not been able to maximize Islamic Religious Education learning at SMA Muhammadiyah 1 Palembang. So that the learning outcomes of Islamic Religious Education get very low scores, therefore it is necessary to have a varied learning model and attract the attention of students so that it will encourage the success of students in mastering the material and improve student learning outcomes. This research is experimental research with Quasy Experimental Design. The samples of this study were 2 classes consisting of 60 students, namely class XII IPA 4 as an experimental class using the Rotating Trio Exchange learning strategy and class XII IPA 5 as a control class using an expository strategy. The sampling technique was carried out by a random system. Data collection techniques using learning outcomes tests and documentation. The instrument used is a multiple-choice written test according to the indicators. Before the question instrument was given, the question had been tested to determine the validity, reliability, discriminatory power, and level of difficulty of the test as a question instrument. Test requirements analysis using normality and homogeneity tests. Technical analysis of data using t-test.